Enhancing High School Students’ Self-Efficacy in Major Selection through CBT-Based Group Guidance with Role-Playing - Rike Ernawati Sinaga; Zadrian Ardi; Nurfarhanah Nurfarhanah; Dina Sukma; Yeni Karneli; Ramdani Ramdani (STAI Hubbulwathan Duri, 2026)
Selecting a university major represents a pivotal developmental task for senior high school students, yet many struggle with uncertainty regarding their academic capabilities. Within this context, self-efficacy, the belief in one's capacity to execute actions necessary to achieve specific goals, plays a critical role in facilitating informed and confident decision-making. This study examines the potential effectiveness of a group guidance intervention integrating Cognitive Behavior Therapy (CBT) principles with role-playing techniques to enhance students' self-efficacy in major selection. Employing a quasi-experimental nonequivalent pretest-posttest control group design, the study involved 11th-grade students at SMAN 20 Batam. Ten participants with moderate baseline self-efficacy levels were assigned to the experimental group through purposive sampling. Data were gathered using a self-efficacy questionnaire adapted from Bandura's (1999) theoretical framework, and analyzed via the Wilcoxon Signed Ranks Test. It is important to note that the results presented herein are based on simulated data, intended to illustrate the proposed analytical procedure and intervention design. Simulation outcomes indicated a statistically significant improvement in self-efficacy scores within the experimental group (p = 0.012), whereas the control group showed no meaningful change (p = 0.230). These findings suggest that CBT-based group guidance incorporating role-playing may serve as a promising strategy for fostering students' confidence in academic decision-making. Practically, this approach offers school counselors and educators a structured, theory-informed module to support adolescents during a critical transitional period. Future research with fully implemented empirical data and larger, randomized samples is recommended to validate these preliminary insights.